Mitotic role for the Cdc28 protein kinase of Saccharomyces cerevisiae. - Reed, S I (1990)
The Cdc28 protein kinase functions in the G1 to S phase transition of the cell cycle of the budding yeast Saccharomyces cerevisiae. This is in contrast with observations of the homologous protein kinase from a variety of metazoans, where activity and function are associated with the G2 to M phase transition. We present evidence that the Cdc28 protein kinase is also required for mitosis and that this function is executed in the G2 interval of the cell cycle. We show, in addition, that the protein kinase is highly active during this phase of the cell cycle. The dual role of the Cdc28 protein kinase in the S. cerevisiae cell cycle thus parallels that demonstrated for the cdc2 protein kinase of the fission yeast Schizosaccharomyces pombe.